Women Undergoing Hormonal Treatments for Infertility: A Systematic Review on Psychopathology and Newly Diagnosed Mood and Psychotic Disorders - González-Rodríguez, Alexandre; Cobo, Jesús; Soria, Virginia; Usall, Judith; Garcia-Rizo, Clemente; Bioque, Miquel; Monreal, José Antonio; Labad, Javier (Frontiers in Psychiatry, 2020)
Background The association between infertility treatments and mental disorders has been poorly addressed. This work aims to review current evidence on the psychopathological effects of hormonal treatments used for infertility on women and the occurrence of newly diagnosed mood and psychotic disorders. Methods A systematic review was performed by searching PubMed and clinicaltrials.gov databases from inception until September 2019. Clinical trials on hormone treatments for infertility in patients with mood or psychotic disorders, as well as those evaluating the onset of symptoms, were included. Selected studies were published in English, Spanish, and Dutch language peer-reviewed journals. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. Observational studies and case reports were excluded. Effect sizes for changes in depressive symptoms were calculated with Hedges’g and Cohen’s d confidence intervals. A meta-analysis was not performed due to the heterogeneity of hormonal compounds in protocols. Results From 1,281 retrieved records, nine trials were included; all of them were conducted in non-clinical populations. Four trials compared Gonadotropin-releasing hormone (GnRH) agonists and GnRH antagonists, showing a better mood profile for hormonal protocols including antagonists in one trial. Two trials compared protocols using GnRH agonists/antagonists versus natural cycle protocols (without gonadotropin stimulation), with a better mood profile (less depressive symptoms) in those protocols without gonadotropin stimulation. Other studies compared long and short protocols of GnRH agonists (no differences); two GnRH agonists, buserelin, and goserelin (no differences); and two patterns of clomiphene vs placebo administration (no differences). None of the selected studies investigated the risk of relapse in women with a previous diagnosis of depressive or psychotic disorders. When exploring pre-post changes in depressive symptoms, effect sizes suggested mild mood worsenings for most protocols (effect sizes ≤ -0.4), with the following pattern (worse to better): GnRH agonist > GnRH antagonist > no gonadotropin stimulation. Conclusions This is the first systematic review exploring the psychopathological effects of hormonal infertility treatments. Our study suggests that protocols without gonadotropin stimulation show a better mood profile when compared to those using GnRH antagonists or GnRH agonists. Future studies need to include patients with major mood and psychotic disorders.